GIZI DAN GIGI LANSIA - Asep Arifin Senjaya (Jurnal Kesehatan Gigi (Dental Health Journal), 2015)
Results of Population Census 2010 indicated that Indonesia among the top five countries with the number of elderly people (elderly) in the world, reaching 18.1 million in 2010 or 9.6% of the population. This encourages us all to be ready to face the logical consequence of the existence of problems - problems that arise due to this elderly population explosion. Elderly often have problems of malnutrition, even though they do not look thin. Increasing age, the higher the risk of suffering from malnutrition. The purpose of writing is to provide information that the teeth play an important role in the digestive process to nutrition to support the health and quality of life of the elderly. Elderly is a natural process that can not be avoided. The function of the teeth is not only limited help chew or speak, but also aesthetics or appearance. Aesthetic functions and still be considered normal talk with the number of teeth at least 20 pieces. In the group of elderly is expected to have a minimum of 20 dental work. Nutritional problems faced by elderly people closely related to the decrease in the biological activity of the body. Less balanced food consumption will worsen the condition of the elderly who naturally was already declining. Reduced ability to digest food due to damage or missing teeth is one of the factors that influence the nutritional needs of the elderly. For the erderly on an ongoing basis: maintaining oral hygiene, diet, and regular dental examinations